2007
DOI: 10.3758/bf03193921
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and categorization of environmental sounds

Abstract: Four experiments investigated the acoustical correlates of similarity and categorization judgments of environmental sounds. In Experiment 1, similarity ratings were obtained from pairwise comparisons of recordings of 50 environmental sounds. A three-dimensional multidimensional scaling (MDS) solution showed three distinct clusterings of the sounds, which included harmonic sounds, discrete impact sounds, and continuous sounds. Furthermore, sounds from similar sources tended to be in close proximity to each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
177
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(198 citation statements)
references
References 43 publications
(61 reference statements)
19
177
1
1
Order By: Relevance
“…Any MDS analysis is limited to a representation of the perceptual distances between items; it does not provide any interpretation of the dimensions, and those dimensions may not have any obvious mapping. As in the MDS space of environmental sounds in Gygi et al (2007), it does not appear that there is any obvious single factor associated with each dimension in our space. What is apparent in both spaces is a clustering of semantically related items.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Any MDS analysis is limited to a representation of the perceptual distances between items; it does not provide any interpretation of the dimensions, and those dimensions may not have any obvious mapping. As in the MDS space of environmental sounds in Gygi et al (2007), it does not appear that there is any obvious single factor associated with each dimension in our space. What is apparent in both spaces is a clustering of semantically related items.…”
Section: Resultsmentioning
confidence: 82%
“…In examining the MDS results of Gygi et al (2007), we saw clear evidence for some semantic clustering, indicating that the MDS procedure does not necessarily provide a pure assessment of psychoacoustic space. As we discuss below, semantic influences on the MDS solution can potentially make it more difficult for us to observe semantic effects on change deafness (i.e., they make our change-deafness experiment more conservative).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Later studies showed that during a free sorting task, the event causing the sound (action/interaction, type of excitation, source) was used more often than acoustic qualities of the sound, as a criterion for categorization [Marcell et al 2000]. Further to this, the event also overrided context and location [Gygi et al 2007], and overrided any shared physical properties when participants focused on the mental image generated by each stimulus [Scavone et al 2002]. When sounds were more complex like sequences of environmental sounds, the categorization was more closely related to global judgment like the absence or presence of human activity [Guastavino 2007].…”
Section: Introductionmentioning
confidence: 99%